Pengaruh Penggunaan Media Big Book Terhadap Hasil Belajar IPA Tema Ekosistem Siswa Kelas V SDN INPRES Perumnas 2 Waena - Purba, Rispah; Silaban, Adeline (ALACRITY : Journal of Education, 2024)
The aim of this research was to determine the influence of the use of Big Book media on science learning outcomes on the ecosystem matter at SDN Inpres Perumnas 2 Waena. This type of research is quantitative research with experimental methods. The population in this study were fifth grade students and the sampling technique was a total sampling of 50 students. The data collection technique uses a test consisting of a pre-test and post-test, each with 20 multiple choice questions. The results of the trial test on 20 students and validity were obtained with r count = 0.765 with a significance level of 5% with rtable = 0.404. Reliability test with index r11 = 0.773 with high category reliability. The difference between questions is in the good and very good categories, while the difficulty level of the questions is in the categories of 25% easy, 50% medium and 25% difficult. Furthermore, the differentiating power of the test was found to be 15% of questions in the very good category, 35% in the good category, 50% in the quite good category. Descriptive data analysis techniques related to the description of the achievement of mastery of science learning outcomes on the ecosystem matter in the low category were 6 people (24%), in the medium category 11 people (44%) and in the high category 8 people (32%). The pre-test and post-test normality tests for the experimental class obtained sig values of 0.286 > 0.05 and 0.156 > 0.05, which means the data is normally distributed. The homogeneity test obtained a significance value of 0.992 > 0.05, which means the data is homogeneous. Test the hypothesis using an independent sample test and obtain a t count of 1.73 and t table = 1.677 because t count > t table then ho is rejected, which means that there is an influence of the use of Big Book media on the science learning outcomes of fifth grade students at SDN Inpres Perumnas 2 Waena.